Quality of life evaluation in NUTS3 regions of Czech Republic and progression of evaluation in years 2000 - 2015 - Šanda, Martin; Mandys, Jan (Masarykova univerzita, 2017)
This paper deals with the quality of life evaluation in NUTS3 regions of Czech Republic and progression of this evaluation in years 2000 - 2015 based on selected indicators of Czech statistical office. The set of indicators is organized along a lot of areas: economy, safety, health, education, infrastructure, environment, labor market and other. Indicators for quality of life evaluation were selected from survey between Czech inhabitants from various regions, age and from different demographic characteristics in august 2016. Quality of life is evaluated by the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The NUTS3 regions of Czech Republic are evaluated by TOPSIS for each year and the result is a ranking of quality of life in regions. Next result is progress of these ranking regions in years 2000 - 2015. The results of QL evaluation show small differences in the assessment of individual regions, even though they are so different.
Hodnocení kvality života krajů České republiky a vývoj tohoto hodnocení v letech 200-2015
Keywords: indicators; quality of life evaluation; NUTS3 regions; TOPSIS; ukazatele; hodnocení kvality života; kraje; TOPSIS